GENERAL PRINCIPLES OF BUILDING THE MODEL OF DEVELOPMENT AND OPERATION OF HETEROGENEOUS TEAMS FOR PROJECT MANAGEMENT - Valeriy Gurin; Elena Persiyanova (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the research is the basic principles of making the model of managing the production of software and models of development and operation of heterogeneous teams for project management. The objective of the research is to develop the mathematical model representing the operation of heterogeneous teams for project management. The sociometry is used for psychodiagnostic procedures in the course of social and psychological analysis of group relations. This method is directed at determining the structure of interpersonal relations by identifying mutual feelings of frienliness and unfrienliness among the members of groups. The mathematical methods of processing data and information obtained during the sociometric survey lie in calculating mathematical indicators which can be subdivided into group and individual indexes. In the course of the research the following taskswere solved: the requirements for team building and development of models for software implementation were analyzed; the method for analyzing the cohesion of team members was selected; the options for developing the mathematical model representing the principles of building the team which works on the project were considered. Groups different in structure were compared with the help of mathematical processing of statistical data; and correlation procedures were conducted. Individual indexes were defined; among them are: the index of sociometric status which indicates the advantage of any member of the group over other participants; the indexes of positive and negative emotional expansivity; the index of group cohesion; the index of sociometric coherence. The methods used are: statistical and correlation analysis, sociological, Hungarian, mathematical. As a result of the conducted researches the basic principles of making the model of managing software development are shown, mathematical methods of development and operation of heterogeneous teams for project management are suggested. Thus, the goals and objectives of the research are carried out.